PENGARUH BUDAYA ORGANISASI DAN PELATIHAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. MITRA PACKINDO BERDIKARI MEDAN - Jemi Jemi; Imanuel Tarigan; Syawaluddin Syawaluddin (STIE-PMCI, 2018)
PT. Mitra Packindo Berdikari Medan is a company engaged in the field of Flexibag Packing. Problems at PT. Mitra Packindo Berdikari Medan that the weak organizational culture and the lack of effective job training applied in the company so that causing employee work productivity decreased. The purpose of this research is to know and analyze the influence of organizational culture and job training on employee work productivity PT. Mitra Packindo Berdikari Medan.This research uses quantitative descriptive research type. The total population and sample in this research are 36 employees. The sampling technique uses saturated sampling technique. Data analysis technique is using multiple linear regression analysis.The results of this study indicate that simultaneously there is a positive and significant influence between organizational culture variables and job training on employee productivity PT. Mitra Packindo Berdikari Medan. Partially there is a positive and significant influence between organizational culture variables and job training on employee productivity PT. Mitra Packindo Berdikari Medan. Organizational culture and job training able to explain employee work productivity equal to 26,1% while the rest 73,9% influenced by variable not examined such as: compensation, promotion, job supervision and so onÂ Keywords: Organizational Culture, Job Training, Work Productivity